Risalah tauhid - Syekh Muhammad Abduh (Bulan Bintang, 1976)
ir,c.1-2/oen, c.3-4,ws.c.5/oen,c.6/ast c.7/ast c.8/oen, c.9/oen, c.10/oen, c.11,ws.c.12/ast 13/oen, c.14/ir,c.15/oen, c.16-18/en, c.19/en, c.20